Rehabilitation for survivors of severe stroke - Mohapatra, Sushmita (2019)
Providing appropriate rehabilitation for stroke survivors with severe disabilities can be challenging. This is due to the magnitude of neurological impairment early after stroke as well as the complexity of delivering long-term care post-hospital discharge. Severe stroke survivors have limited access to rehabilitation as a likely result of uncertainty related to their potential for functional gains. They are also likely to require greater health and social care resources for long-term care with significant cost implications. Rehabilitation following stroke has been proven beneficial after a severe stroke; however, recovery remains ambiguous. Several clinical and non-clinical factors are evidenced to influence the provision of rehabilitation interventions. However, it is not known how the decisions are made in practice for service provision, what service they receive and how they relate to the stroke survivors’ recovery and rehabilitation.